2011
DOI: 10.1021/jm200388e
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the in Vitro Cardiac Safety of Hydroxamate-Based Histone Deacetylase Inhibitors

Abstract: Histone deacetylase (HDAC) inhibitors have shown promise in treating various forms of cancer. However, many HDAC inhibitors from diverse structural classes have been associated with QT prolongation in humans. Inhibition of the human ether a-go-go related gene (hERG) channel has been associated with QT prolongation and fatal arrhythmias. To determine if the observed cardiac effects of HDAC inhibitors in humans is due to hERG blockade, a highly potent HDAC inhibitor devoid of hERG activity was required. Starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 72 publications
0
38
0
1
Order By: Relevance
“…Outside of the ability of HDAC3 to regulate genomic stability (7), mouse knockout studies have also shown that HDAC3 is necessary for maintenance of several metabolic functions in both cardiac and hepatic tissues (38, 39). One particular problem with current clinically available HDAC inhibitors is that they also bind and inhibit the hERG ion channel, which has been linked with QT prolongation (40). This off-target binding can lead to cardiac arrhythmia and is potentially fatal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of the ability of HDAC3 to regulate genomic stability (7), mouse knockout studies have also shown that HDAC3 is necessary for maintenance of several metabolic functions in both cardiac and hepatic tissues (38, 39). One particular problem with current clinically available HDAC inhibitors is that they also bind and inhibit the hERG ion channel, which has been linked with QT prolongation (40). This off-target binding can lead to cardiac arrhythmia and is potentially fatal.…”
Section: Discussionmentioning
confidence: 99%
“…This off-target binding can lead to cardiac arrhythmia and is potentially fatal. Newer inhibitors are now being screened not only for their abilities to block HDAC function, but also for their abilities to block hERG activity as well (40, 41). An HDAC inhibitor that structurally cannot inhibit HDAC3 and cannot bind hERG, then, would be of considerable therapeutic interest.…”
Section: Discussionmentioning
confidence: 99%
“…These multiple pathways occurring alone and in multiple combinations lead to the observed complexity. Knowledge of the soft spot of metabolism contributed to the design of novel deacetylase inhibitors with improved metabolic properties and no doselimiting cardiac effects (Shultz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The greatest cardio-toxicity is, however, observed after treatment with hydroxamic-derivative HDACi. Again, it is unclear as to whether hydroxamic derivatives interact preferentially with (hERG)K + channels or whether their broad-spectrum activity against all HDACs could exacerbate cardiac side effects (195).…”
Section: Side Effects Of Hdacimentioning
confidence: 99%